2015
DOI: 10.3892/ijmm.2015.2178
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 transgenic mice as an in vivo model of congenital heart disease

Abstract: Our previous study indicated that 8 patients from a family with a history of congenital heart disease had simple atrial septal defect (ASD) and carried the same mutation at codon 310 in the GATA4 gene. In the present study, to identify the functional defects caused by this mutation in an in vivo model, the transgene DNA constructs were microinjected into mice to generate a transgenic mouse model. The mice were genotyped using PCR and DNA sequencing. Protein expression was measured by western blot analysis. qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This mutation impairs GATA4's interaction with another ZF protein FOG2 . Finally, transgenic Gata4 mice with the M310V atrial septal defect (ASD) causing mutation show impairment in GATA4 ability to activate downstream myocardial promoters …”
Section: Congenital Heart Diseases and Gata Mutationsmentioning
confidence: 99%
“…This mutation impairs GATA4's interaction with another ZF protein FOG2 . Finally, transgenic Gata4 mice with the M310V atrial septal defect (ASD) causing mutation show impairment in GATA4 ability to activate downstream myocardial promoters …”
Section: Congenital Heart Diseases and Gata Mutationsmentioning
confidence: 99%
“…Several well-established cardiac transcription factors that are highly expressed in cardiogenic plates such as NKX2.5, GATA4, and TBX5 have been extensively studied in both human [47] and animal experiments [48,49]. Mutations in these cardiac transcription factors are associated with most non-syndromic CHDs [50].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Han et al explored the role of GATA4 M310 V mutation in CHD development utilizing GATA4 transgenic mice, and the results showed that this polymorphism was significantly correlated with the disease development. [ 21 ] According to the report of Sanchez-Castro et al, the upstream deletions of transcription factor gene SRY-box transcription factor 9 ( SOX9 ) might contribute to the pathogenesis of CHD. [ 22 ]…”
Section: Resultsmentioning
confidence: 99%